Amber Heard’s Histrionic Personality Disorder Tendencies on Representative Illocutionary Act Utterances Analysis in Trial Court - Munanov, Ressa Rahmadita; Rosita, Nur (Universitas Negeri Padang, 2024)
This research aims to find the representative illocutionary act utterances and what histrionic personality disorder tendencies might affect the representative utterances Amber Heard uttered in trial court. This research used the descriptive-qualitative method, using Searle (1976) theory of a classification of illocutionary act to determine the representative illocutionary act utterances and Diagnostic and Statistical Manual of Mental Disorder, fifth edition by American Psychiatric Association (2013) to find the indication of histrionic personality disorder tendencies affecting representative utterances. This research found 63 data with 5 types of representative illocutionary act found, dominated by stating. This because Amber Heard was required to answers the questions based on what she knows and believed. Meanwhile some of the representative utterances indicated 5 diagnostic criteria found in 20 data from 17 representative utterances, dominated by display rapidly shifting and shallow expression of emotion . This is due to Amber Heard’s need to show how her experience feel to the other parties, as well as her career as an actress might be the other reason. This research only show the probability of HPD tendencies affected Amber Heard representative illocutionary act utterances, and not to diagnosed Amber Heard with any of personality disorder without clinical assessment.